PENGARUH MODEL NUMBERED HEAD TOGETHER TERHADAP KERJA SAMA SISWA PADA PEMBELAJARAN IPS KELAS V SD - Ervain Andika Tsaqif; Fajar Nugraha; Hatma Heris Mahendra (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
This study aims to analyze the effect of the Numbered head together (NHT) cooperative learning This study aims to analyze the effect of the Numbered Head Together (NHT) cooperative learning model on students’ collaboration skills in Social Studies (IPS) among fifth-grade elementary school students. The study employed a quantitative approach with a quasi-experimental non-equivalent control group design. The research subjects consisted of fifth-grade students of SDN Sukamulya in the 2025/2026 academic year, with Class V A serving as the experimental group and Class V B as the control group, each comprising 30 students. The research instrument was a collaboration skills observation sheet validated through expert judgement and tested for reliability using SPSS. Data were analyzed through normality tests, homogeneity tests, and independent t-tests. The results indicated that the mean post-test collaboration score reached 15.04. The independent t-test showed a Sig. value (2-tailed) of 0.823 > 0.05, indicating no significant difference between the experimental and control groups following the treatment. Nevertheless, descriptive data showed an increase in scores in the experimental group compared to the control group, suggesting a positive tendency of the NHT model toward the development of students’ collaboration skills. Therefore, it can be concluded that there was no statistically significant effect of the NHT model on students’ collaboration skills in Social Studies learning. However, descriptive findings indicated improvements in the experimental group, implying that the NHT model still holds potential to enhance collaboration skills when accompanied by longer treatment duration and a supportive learning environment. ABSTRAK Penelitian ini bertujuan untuk menganalisis pengaruh model pembelajaran Numbered head together (NHT) terhadap kemampuan kerja sama siswa pada pembelajaran Ilmu Pengetahuan Sosial (IPS) kelas V SD. Penelitian ini menggunakan pendekatan kuantitatif dengan desain quasi eksperimen non-equivalent control group. Subjek penelitian adalah siswa kelas V SDN Sukamulya tahun ajaran 2025/2026, dengan kelas V A sebagai kelompok eksperimen dan kelas V B sebagai kelompok kontrol, masing-masing berjumlah 30 siswa. Instrumen penelitian berupa lembar observasi kemampuan kerja sama yang divalidasi melalui expert judgement dan diuji reliabilitas menggunakan SPSS. Data dianalisis melalui uji normalitas, homogenitas, dan uji-t independen. Hasil penelitian menunjukkan bahwa rata-rata skor post-test kemampuan kerja sama siswa mencapai 15,04. Uji-t independen menunjukkan nilai Sig. (2-tailed) 0,823 > 0,05, sehingga tidak terdapat perbedaan signifikan antara kelas eksperimen dan kelas kontrol setelah perlakuan. Meskipun demikian, data deskriptif menunjukkan adanya peningkatan skor pada kelompok eksperimen dibandingkan kelompok kontrol, yang mengindikasikan kecenderungan positif terhadap pengembangan kemampuan kerja sama siswa melalui model pembelajaran NHT. Dengan demikian, dapat disimpulkan bahwa tidak terdapat pengaruh yang signifikan secara statistik dari penerapan model pembelajaran NHT terhadap kemampuan kerja sama siswa pada pembelajaran IPS. Namun demikian, temuan deskriptif menunjukkan adanya peningkatan skor pada kelompok eksperimen dibandingkan kelompok kontrol, sehingga model pembelajaran NHT tetap memiliki potensi dalam mengembangkan kemampuan kerja sama siswa apabila disertai durasi perlakuan yang lebih panjang serta dukungan lingkungan belajar yang memadai.